Impacto de práticas agrícolas sobre a produtividade de grãos e propriedades físicas e químicas de solos cauliníticos dos tabuleiros costeiros de Sergipe - Thimothée, Jean Alex (2019)
Kaolinitic soils, typical of coastal tablelands, have a fragile physical structure and are very vulnerable to degradation by corn production systems used in Agreste of Sergipe, characterized by preparation with soil revolving and low input of plant residues. Thus, despite the high potential of corn production in this region, alternatives for soil preparation and crop management and plant cover are essential to promote the agricultural sustainability of the region. The objective of this study was to quantify the effect of different agricultural practices on grain productivity and soil quality in the coastal tablelands of Agreste of Sergipe. The study was conducted in an experiment in randomized blocks, with four repetitions, at the Jorge Sobral Experimental Camp, in Nossa Senhoras das Dores, SE. Ten treatments, with combinations between the factors of crop (corn vs soybean), soil tillage method (conventional, CT, vs. no-tillage, NT), cultivation system (monoculture vs. crop rotation), integration of corn with brachiaria (with or without integration) and species of brachiaria in integration (B. decumbens vs. B. ruziziensis) were evaluated for yield of corn and soybean grains, in the years 2017 and 2018, and the following soil quality descriptors in 2018: mean diameter of soil aggregate (DSA) and water aggregate stability (WAS) and organic matter content (MOS). Analysis of variance of orthogonal contrasts, consisting of treatments comparing different agricultural practices, was used to quantify the relative effect of each of these practices on soil quality and corn and soybean yield. No-till (NT) presented higher values of DSA and WAS than in conventional tillage (CT). In CT, crop rotation promoted higher DSA values, compared to the average of corn and soybean monocultures. Soil tillage method, integration of grain cultivation with brachiaria, as well as rotation of crop systems affect grain yield. The highest effect observed was associated with the use or not of brachiaria in grain production systems, since the presence of brachiaria increased corn and soybean yields by 45% and 135%, respectively. The integration of brachiaria with corn in rotation with soybean exerts influence on the yield of grains, since it directly influences the formation of straw and, consequently, the efficiency of the mulch, being a viable technology for grain crops in no-till system.